2018
DOI: 10.1097/meg.0000000000001224
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography can stratify patients with Child–Pugh A cirrhosis according to risk of early decompensation

Abstract: The risk of liver decompensation increased with increasing LSM in mixed aetiology compensated cirrhosis. LSM may be used to risk stratify patients, potentially reassure patients with low scores, and select patients with higher scores for experimental therapeutic studies with acceptable timelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…We included patients who had a previous episode of decompensation but remained fully compensated for at least 6 months prior to enrolment. Previous work has shown that previous decompensation had no difference on LSM measurement or liver related outcome at 2 years, and in this study we show similar lack of impact.…”
Section: Discussionmentioning
confidence: 99%
“…We included patients who had a previous episode of decompensation but remained fully compensated for at least 6 months prior to enrolment. Previous work has shown that previous decompensation had no difference on LSM measurement or liver related outcome at 2 years, and in this study we show similar lack of impact.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Similarly, TE showed a prognostic role in predicting the risk of HCC, decompensation and LRE development. 8,16,17,19,21,[36][37][38][39][40][41] In this multicentre, retrospective, large cohort study (n = 9300) with a long-term follow-up period (median: 60.0 months), we assessed the risk of HCC and LRE development using US and TE and investigated whether the combined use of US and TE could be beneficial for the risk assessment of HCC and LRE in patients with CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several clinical implications. First, the cumulative incidence rates of HCC increased in the order of US(+)TE(+), US(−) Although previous studies have examined the correlation between fibrotic burden measured by either US or TE and the risks of HCC or LRE development, 8,16,17,19,21,[35][36][37][38][39][40][41] little is known about the prognostic value of the combined use of US and TE. Our study suggests that the combined use of these diagnostic modalities might be more helpful for providing a detailed prognostication than the use of a single modality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations